Preferential Y-Y pairing and synapsis and abnormal meiotic recombination in a 47, XYY man with non obstructive azoospermia. Issue 1 (December 2016) - Wu, Caiyun; Wang, Liu; Iqbal, Furhan; Jiang, Xiaohua; Bukhari, Ihtisham; Guo, Tonghang; Yin, Gengxin; Cooke, Howard; Cao, Zhenyi; Jiang, Hong; Shi, Qinghua
Abstract Back ground Men with 47, XYY syndrome are presented with varying physical attributes and degrees of infertility. Little information has been documented regarding the meiotic progression in patients with extra Y chromosome along with the synapses and recombination between the two Y chromosomes. Methods Spermatocyte spreading and immunostaining were applied to study the behavior of the extra Y chromosome during meiosis I in an azoospermia patient with 47, XYY syndrome and results were compared with five healthy controls with proven fertility. Results The extra Y chromosome was present in all the studied spermatocytes of the patient and preferentially paired and synapsed with the other Y chromosome. Consistently, gamma-H2AX staining completely disappeared from the synapsed regions of Y chromosomes. More interestingly, besides recombination on short arms, recombination on the long arms of Y chromosomes was also observed. No pairing and synapsis defects between homologous autosomes were detected, while significantly reduced recombination frequencies on autosomes were observed in the patient. The meiotic prophase I progression was disturbed with significantly increased proportion of leptotene, zygotene cells and decreased pachytene spermatocytes in the patient when compared with the controls. Conclusions These findings highlight the importance of studies on meiotic behaviors in patients with an abnormal chromosomal constitution and provide an important framework for future studies, which may elucidate the impairment caused by extra Y chromosome in mammalian meiosis and fertility.